2012
DOI: 10.1002/smj.1980
|View full text |Cite
|
Sign up to set email alerts
|

Does it pay to be really good? addressing the shape of the relationship between social and financial performance

Abstract: Building on the theoretical argument that a firm's ability to profit from social responsibility depends upon its stakeholder influence capacity (SIC), we bring together contrasting literatures on the relationship between corporate social performance (CSP) and corporate financial performance (CFP) to hypothesize that the CSP‐CFP relationship is U‐shaped. Our results support this hypothesis. We find that firms with low CSP have higher CFP than firms with moderate CSP, but firms with high CSP have the highest CFP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
534
5
17

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 958 publications
(587 citation statements)
references
References 47 publications
31
534
5
17
Order By: Relevance
“…The inverse U-shape we found also opposes findings of a positive U-shape in previous research, most notably in Barnett and Salomon (2012). However, this study used a comprehensive measure of social performance (based on KLD data) that conflates outcome and process dimensions.…”
Section: --------------------------------Insert Figure 1 About Here -contrasting
confidence: 83%
See 3 more Smart Citations
“…The inverse U-shape we found also opposes findings of a positive U-shape in previous research, most notably in Barnett and Salomon (2012). However, this study used a comprehensive measure of social performance (based on KLD data) that conflates outcome and process dimensions.…”
Section: --------------------------------Insert Figure 1 About Here -contrasting
confidence: 83%
“…In the other model, they associated high financial performance with either very high or very low levels of social performance, implying a U-shaped curve. Subsequently, Barnett and Salomon (2012) found evidence of a U-shaped relationship between social and financial performance. In particular, they observed that benefits vary across the range of corporate social performance, such that when the capacity to influence stakeholders accumulates, benefits are generated that balance and then exceed the costs of socially responsible initiatives.…”
Section: Environmental Performance: Non-linear Effects On Financial Pmentioning
confidence: 99%
See 2 more Smart Citations
“…In parallel with the various corporate social responsibility qualification and rating agencies (e.g., Ethical Investment Research Services -EIRIS-, Sustainable Asset Management -SAM-, Sustainable Investment Research International -SiRi-, Forum Ethibel), several investment funds and stock market indexes feature only businesses that comply with strict environmental and social demands (e.g., FTSE4Good Index, Dow Jones Sustainability Index, Domini 400 Social Index; EscrigOlmedo, Muñoz-Torres & Fernandez-Izquierdo, 2013). Furthermore, as previous research has suggested, firms' financial performance might benefit from their environmental and social responsibility, according to the direct positive association of corporate environmental and social performance (CESP) with financial performance (Barnett & Salomon, 2012;Margolis, Elfenbein & Walsh, 2007;Orlitzky, Schmidt & Rynes, 2003).…”
Section: Introductionmentioning
confidence: 99%